2015
DOI: 10.4172/2157-7145.1000299
|View full text |Cite
|
Sign up to set email alerts
|

Facial Soft Tissue Thickness in Forensic Facial Reconstruction: Is it enough if Norms Set?

Abstract: Facial reconstruction relies on the relationships between the facial features, subcutaneous soft tissues and underlying bony structure of the skull. If there is no clue for potential identity because of impossibility to compare questioned remains with possible familiar material, in such cases one of the last chances is to recreate ante mortem appearance by face reconstruction. Many of the soft tissue thickness values are significantly different from those reported for comparable groups, suggesting that individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Lateral cephalometric radiography, which generates a lateral cephalogram, shows dental, skeletal, and soft tissue profiles, and is used to determine dental and skeletal relationships, with the aim of planning orthodontic treatment [ 33 ]. More contemporary methods for determining FSTT have recently been developed [ 14 , 23 ], including computed tomography (CT) scanning [ 35 ], cone beam CT (CBCT) [ 17 , 19 ], ultrasonography [ 4 ], and magnetic resonance imaging (MRI) [ 18 , 22 ]. Needle puncture measurements of FSTT have been reserved for cadaveric studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lateral cephalometric radiography, which generates a lateral cephalogram, shows dental, skeletal, and soft tissue profiles, and is used to determine dental and skeletal relationships, with the aim of planning orthodontic treatment [ 33 ]. More contemporary methods for determining FSTT have recently been developed [ 14 , 23 ], including computed tomography (CT) scanning [ 35 ], cone beam CT (CBCT) [ 17 , 19 ], ultrasonography [ 4 ], and magnetic resonance imaging (MRI) [ 18 , 22 ]. Needle puncture measurements of FSTT have been reserved for cadaveric studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aggarwal and Singla reported on the presence of significant differences between men and women, and men had increased values for FSTT for the labrale superius, labrale inferius, pogonion and menton, compared with women, and recommended that this difference should be taken into consideration when planning orthodontic therapy [ 30 ]. Hamid and Abuaffan [ 4 ], Ramesh et al [ 5 ], Chen et al [ 22 ], Atashi et al [ 38 ], and Masoumeet et al [ 17 ] have all shown differences in FSTT between men and women, but have given the explanation as being due to the influence of body mass index (BMI). Karnaket et al [ 27 ], and Maurya et al [ 39 ] found significant differences between men and women in the area of the labrale superius and pogonion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations